Perlindungan Hukum Pembeli Beritikad Baik dalam Sengketa Kepemilikan Hak atas Tanah (LEGAL DIALOGICA, 2025)
This study aims to examine the regulations governing protection for good faith buyers in land ownership disputes and analyze how effective the existing legal protection mechanisms are in protecting the rights of good faith buyers.This study uses a normative research type with a statutory approach. With the aim of analyzing the legal aspects that are bound by the object of research.The results of this study explain 2 objectives, namely: (1) To examine the regulations governing protection for good faith buyers in land ownership disputes; (2) To analyze how effective the existing legal protection mechanisms are in protecting the rights of good faith buyers. Based on the results of the study, the following conclusions were obtained: (1) A good faith buyer is a party who legally purchases land without knowing that there is a dispute. Indonesian law, through the UUPA and the Civil Code, protects their rights as long as the transaction procedure is carried out correctly. In cases of dispute, such as Decision No.22/Pdt.G/2013/PN, bona fide buyers are still recognized and protected; (2) Legal protection for good faith buyers is determined by the fulfillment of legal procedures, such as proof of ownership, sale and purchase before a PPAT, and the absence of disputes on the land object. Good faith buyers are protected by law based on Article 1338 paragraph (3) of the Civil Code and MA Circular Letter No. 4 of 2016.Recommendations for this study include a legal analysis of the implementation of Article 1338 paragraph (3) of the Civil Code and MA Circular Letter No. 4 of 2016, especially in the protection of good faith buyers. This study can also include case studies on several land sale and purchase disputes to understand the obstacles in proving good faith in court. In addition, comparative legal research with other countries will help find best practices in protecting good faith buyers. Research can also examine the effectiveness of the role of PPAT in ensuring the legality of land sales and purchases and its impact on legal protection for buyers.Abstrak: Penelitian ini menggunakan jenis penelitian normatif dengan pendekatan undang-undang. Dengan tujuan untuk menganalisis aspek hukum yang terikat dengan objek penelitian. Hasil penelitian ini menjelaskan 2 tujuan yaitu : (1) Untuk Mengkaji regulasi yang mengatur perlindungan bagi pembeli beritikad baik dalam sengketa kepemilikan hak atas tanah; (2) Untuk Menganalisis seberapa efektif mekanisme perlindungan hukum yang ada dalam melindungi hak pembeli beritikad baik. Berdasarkan hasil penelitian, maka diperoleh kesimpulan sebagai berikut : (1) Pembeli beritikad baik adalah pihak yang membeli tanah secara sah tanpa mengetahui adanya sengketa. Hukum Indonesia, melalui UUPA dan KUHPerdata, melindungi hak mereka selama prosedur transaksi dilakukan dengan benar. Dalam kasus sengketa, seperti Putusan No.22/Pdt.G/2013/PN, pembeli bonafide tetap diakui dan dilindungi; (2) Perlindungan hukum bagi pembeli beritikad baik ditentukan oleh pemenuhan prosedur sah, seperti pembuktian kepemilikan, jual beli di hadapan PPAT, dan tidak adanya sengketa pada objek tanah. Pembeli beritikad baik dilindungi hukum berdasarkan Pasal 1338 ayat (3) KUHPerdata dan Surat Edaran MA No. 4 Tahun 2016.Rekomendasi penelitian ini meliputi analisis yuridis tentang implementasi Pasal 1338 ayat (3) KUHPerdata dan Surat Edaran MA No. 4 Tahun 2016, khususnya dalam perlindungan pembeli beritikad baik. Studi ini juga dapat mencakup penelitian kasus pada beberapa sengketa jual beli tanah untuk memahami kendala dalam membuktikan itikad baik di pengadilan. Selain itu, penelitian perbandingan hukum dengan negara lain akan membantu menemukan praktik terbaik dalam perlindungan pembeli beritikad baik. Penelitian juga dapat mengkaji efektivitas peran PPAT dalam memastikan legalitas jual beli tanah serta dampaknya terhadap perlindungan hukum pembeli.